2017
DOI: 10.1002/oby.21720
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver promotes fibrosis in monkeys consuming high fructose

Abstract: Objective Non-alcoholic fatty liver diseases (NAFLD) are related to development of liver fibrosis which currently has few therapeutic options. Rodent models of NAFLD inadequately model the fibrotic aspects of the disease and fail to demonstrate the spectrum of cardiometabolic diseases without genetic manipulation. We aimed to document a monkey model of fatty liver and fibrosis, which naturally develop cardiometabolic disease pathophysiologies. Methods We studied 27 cynomologus monkeys (Macaca fascicularis) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…In one study in cynomolgus monkeys ( M. fascicularis ), the administration of fructose was shown to result in both an increase in liver fat and hepatic fibrosis after seven years, with the degree of fibrosis correlating with time of fructose exposure (42). Fructose-induced metabolic syndrome can also be induced in rhesus monkeys (43).…”
Section: Soft Drinks and Added Sugar Are Associated With Fatty Livermentioning
confidence: 99%
“…In one study in cynomolgus monkeys ( M. fascicularis ), the administration of fructose was shown to result in both an increase in liver fat and hepatic fibrosis after seven years, with the degree of fibrosis correlating with time of fructose exposure (42). Fructose-induced metabolic syndrome can also be induced in rhesus monkeys (43).…”
Section: Soft Drinks and Added Sugar Are Associated With Fatty Livermentioning
confidence: 99%
“…A very recent study 23 on 27 cynomolgus monkeys ( Macaca fascicularis ) over 7 years demonstrated that high-carbohydrate diets alone can generate both liver fat and fibrosis. The monkeys were fed diets with two diets: a control diet (CTL, n=10) or an HFr diet (n=17).…”
Section: Animal Studiesmentioning
confidence: 99%
“…[89][90][91][92][93][94] Specifically, monkey predisposed to MetS (MetS-predisposed) could be an excellent model for NAFLD, which exhibits a higher body weight than healthy individual. [89][90][91][92][93][94] Specifically, monkey predisposed to MetS (MetS-predisposed) could be an excellent model for NAFLD, which exhibits a higher body weight than healthy individual.…”
Section: Other Animal Modelsmentioning
confidence: 99%